2021
DOI: 10.1038/s41563-021-00974-9
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Investigating the nature of active forces in tissues reveals how contractile cells can form extensile monolayers

Abstract: In the version of this Article originally published, the captions for Extended Data Figs. 1, 2 and 3 were in the wrong order and did not correspond to their associated figures. The correct captions are listed below and the Article has been corrected accordingly. In addition, the cell line MCF7 was mistakenly written as 'MCF7A' in seven instances in the main text, Methods and Extended Data Fig. 4 caption, and as 'MCF10A' in one instance in the ' Author contributions' section; these errors have now been correcte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…An example for the normalized average isotropic stress field corresponding to and is shown in Figure 5c , where , with representing the average field during defect lifetime, for all nucleated defects, and is the maximum of the average field. This is in agreement with experimental measurements on epithelial monolayers ( Saw et al, 2017 ; Balasubramaniam et al, 2021 ), with a compressive stress region near the head of the defect and a tensile region near the tail. Interestingly, there is an asymmetry in the intensity of stress in the compressive region at the head of the comet as opposed to the tensile region at the tail (≈5× higher).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…An example for the normalized average isotropic stress field corresponding to and is shown in Figure 5c , where , with representing the average field during defect lifetime, for all nucleated defects, and is the maximum of the average field. This is in agreement with experimental measurements on epithelial monolayers ( Saw et al, 2017 ; Balasubramaniam et al, 2021 ), with a compressive stress region near the head of the defect and a tensile region near the tail. Interestingly, there is an asymmetry in the intensity of stress in the compressive region at the head of the comet as opposed to the tensile region at the tail (≈5× higher).…”
Section: Resultssupporting
confidence: 92%
“…Specifically, cells actively coordinate their movements through mechanosensitive adhesion complexes at the cell–substrate interface and cell–cell junctions. Moreover, cell–cell and cell–substrate adhesions seem to be coupled ( Balasubramaniam et al, 2021 ), further complicating the interplay of mechanics with biochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, motile topological defects, regions where the long axes of the cells take comet or trefoil-like configurations (Fig. 1(b)(c)), have been identified in several confluent cell layers [23][24][25][26]. This is reminiscent of active turbulence, which is the dynamical behaviour of many active nematic materials, such as suspensions of microswimmers [27,28] or microtubules driven by motor proteins [27].…”
mentioning
confidence: 95%
“…MDCK cells that are on average isotropic in shape [25]. Moreover the comet defects can move towards their head, corresponding to extensile driving [30], even though individual cells are contractile [24]. Indeed, experiments and simulations have shown that the defect motion changes direction -indicating a change from extensile to contractile behaviour -as the cell-cell adhesion is varied.…”
mentioning
confidence: 99%
“…The migration was analyzed for 7 h, because the DNA linker was mainly internalized at this point (Figure S6E). The expression of SNAP-E-cadherin resulted in a decreased correlation length of 135.8 ± 6.2 μm compared to cells expressing E-cadherin-GFP (159.4 ± 7.9 μm), in line with recent reports. , The correlation length could be recovered completely through addition of the DNA linker (157.7 ± 10.9 μm, Figure E). The increased coordination between migrating cells demonstrated a large-scale transduction of mechanical forces , facilitated by the DNA-E-cadherin hybrid system.…”
mentioning
confidence: 99%